Insights into abdominal structures atozoal ultrastructure of coffee berry borer, Hypothenemus hampei (Coleoptera: Curculionidae: Scolytinae) - Poolprasert, Pisit; Charoenphon, Natthawut; Kenthao, Anan; Sornying, Peerapon; Thaochan, Narit (Agriculture and Natural Resources, 2025)
Importance of the work: The coffee berry borer, Hypothenemus hampei is an insect pest of coffee worldwide; however, its abdominal ultrastructure remains undescribed, despite its importance for informing targeted strategies to reduce its population and economic impact. Objectives: To describe, using light and transmission electron microscopy (TEM), the structure of the abdominal region of H. hampei with a focus on the ultrastructure of the spermatozoa. Materials and Methods: A sample of 20 mature male H. hampei, each with a total length of 0.5–1.2 mm, was collected and processed using TEM. Results: The epithelial ultrastructure of the midgut comprised enterocytes and regenerative cells. Numerous mitochondria and lysosomes were observed together with well-developed rough endoplasmic reticulum in the enterocytes. Abundant lipid droplets and glycogen molecules were scattered in the cytoplasm of lipid cells, which were mostly found close to the integument. Testicular maturation was associated with the appearance of spermatids and spermatozoa. The elongated spermatozoon was composed of a head that had two main layers (an acrosomal layer and a central nucleus), a midpiece of elongated and twisted mitochondria and a tail with a typical 9 + 9 + 2 flagellar axoneme. Main finding: The presence of uniflagellate and biflagellate forms not only sheds light on insect evolution and phylogeny but also raises questions about their functional role in the reproductive success of H. hampei.